HESISTATION NOISES AND FILLED PAUSES ANALYSIS USED BY BART AND HOMER IN THE SIMPSON - Veronika Listi Ferdini Damopolii (Universitas Khairun, 2020)
The research explores hesistation Noises Used suggested by McManis, et al (1988). The goals of the of the analysis are to know the hesistation noises used by the speaker and to find out speaker meaning and intention by using those hestitation noises.The research uses a qualitative descriptive method. The data analyzed by using pragmatic approach. The speaker uses hesistation noises : Uh, Umm, Ehm, Uh-uh, and Uh. The speakers use those hesistation noises to show uncertainty and fear, thinking, feeling clumsy and confused, agreement or understanding, and recalling.